Analysis of Inefficiency in Management Systems (Case Study: Rayani Air) - Binti Md Hassan, Siti Nurbalqis; Kee, Daisy Mui Hung; Binti Mohamed Elias, Nur Sarah Solehah; Binti Wan Shafie, Wan Nor Shafinaz; Binti Ahmad Shukri, Shahira; AlAjmi, Danah (AIBPM Publisher, 2019)
Air transportation have become one of the fastest growing industries because of the economic deregulation. This situation makes airlines company started to think out of the box to create an exciting business strategy in order compete in the market. The aim of this study is to investigate the inefficiency of Rayani Air’s management system. Rayani airline is an airlines services that operated in Malaysia. It is the fourth airline in the world that has made it mandatory that each of the Muslim cabin crew be sharia compliant. Unfortunately, there are negative comments about their inefficiency of the systems by customers. Through observation and analysis of existing branding design, this study attempts to develop a new strategy for improving Rayani Air’s management system. In this case, improvement in this system is necessary for restoring consumers’ trust and convincing stakeholders to invest in the company. We conclude that rebranding for failure organization is a crucial task and should be given the highest priority.